Association Between Polymorphisms in Estrogen Receptor Genes and Depression in Women: A Meta-Analysis - Li, Cuifen; Xie, Manli; Wang, Weiwei; Liu, Yanyan; Liao, Dan; Yin, Jingwen; Huang, Hao (Frontiers in Genetics, 2022)
Objective: It is suggested that estrogen receptors (ERs) might be associated with the disproportionate vulnerability of women to depressive episodes. Several variants in ER-alpha (ERα) and ER-beta (ERβ) have been linked to depression, but the results were not consistent. Hence, we conducted a meta-analysis to evaluate the association between ERα/ERβ and depression in a cohort of women. Methods: A comprehensive literature search was performed in public databases. The genetic association between polymorphisms in Erα/ERβ and depression risk in a cohort of women was evaluated by odds ratios (ORs) and 95% confidence intervals (CIs). Cochran’s Q test and the I2 index were used to evaluate heterogeneity. Results: In total, 10 studies and 4 SNPs (rs2234693, rs9340799, rs4986938, rs1256049) were included in meta-analysis. rs2234693 genotype was significantly associated with the risk of depression in women by dominant model (CC + CT vs. TT, OR = 1.30, 95% CI: 1.09-1.55, P = 0.0031), recessive model( CC vs. CT + TT, OR = 1.64, 95% CI: 1.00-2.67, P = 0.0478), additive model (CC vs. TT, OR = 1.93, 95% CI: 1.12-3.35, P = 0.0189) and allelic model (C vs. T, OR = 1.24, 95% CI: 1.10-1.39, P = 0.0003). For rs9340799, the frequencies of risk genotypes according to the dominant (GG + GA vs. AA, OR = 1.47, 95% CI = 1.10-1.98, P = 0.0096, I2 = 0%, P = 0.43) and allelic (G vs. A, OR = 1.33, 95% CI: 1.04-1.69, P = 0.0236, I2 = 0%, P = 0.39) models were significantly lower in women with depression than in controls within the Asian subgroup. For rs1256049, risk genotypes were significantly under the dominant model (AA + GA vs. GG, OR = 1.62, 95% CI: 1.19-2.21, P = 0.0024) and the allelic model (A vs. G, OR = 1.35, 95% CI: 1.07-1.72, P = 0.012) after sensitivity analysis by omitting one study which induce the heterogeneity. Conclusions: The current meta-analysis is the first and most comprehensive investigation of the association between ERs and depression in women, and the findings support the concept that ERs participate in the etiology of sex heterogeneity in depression.